(untitled) - Daskalopoulos, Panagiota (Germany, 2007)
The book deals with the existence, uniqueness, regularity, and asymptotic behavior of solutions to the initial value problem (Cauchy problem) and the initial-Dirichlet problem for a class of degenerate diffusions modeled on the porous medium type equation
Keywords: Boundary value problems,Những vấn đề của giá trị giới hạn